Recent advancements in the diverse roles of polymerase-associated proteins in the replication and pathogenesis of Newcastle disease virus - Jinghang Zhou; Yuqi Duan; Menglan Liu; Jinyang Liu; Zenglei Hu; Zhiqiang Duan (Veterinary Research)
Abstract Newcastle disease virus (NDV) is a significant member of the Paramyxoviridae family, known for causing epidemics and substantial economic losses in the poultry industry worldwide. The NDV RNA genome primarily encodes six structural proteins (N, P, M, F, HN, and L) and two non-structural proteins (V and W). Among these, the polymerase-associated proteins (N, P, and L) and the viral RNA (vRNA) genome form the ribonucleoprotein complex, which plays a crucial role in the synthesis and transcription of NDV vRNA. In the last two decades, numerous studies have demonstrated that the polymerase-associated proteins are linked to the virulence, pathotype, and thermostability of NDV. Additionally, the interactions between these polymerase-associated proteins and host proteins are closely related to the NDV’s replication and pathogenicity. Despite significant progress in understanding the unique and shared functions of NDV polymerase-associated proteins, research on these viral proteins’ structure and function is less comprehensive than other NDV proteins, and the available information is often scattered. Therefore, this article systematically summarises and reviews the research progress made in understanding the structural features, virulence, pathotype, and thermostability correlation of NDV polymerase-associated proteins, as well as the critical roles of interactions between polymerase-associated proteins and host proteins in NDV replication and pathogenicity. This review aims to enhance our understanding of the complex functions of polymerase-associated proteins in NDV replication and pathogenesis and to contribute to the development of more effective vaccines and antiviral drugs against NDV challenges.